Applying the principles of social constructivist theory in teaching the Arabic language – The fourth year of primary education as a model - Bouhamla , Amar (El Omda in Linguistics and Discourse Analysis, 2025)
The article aims to determine the extent to which the principles of this theory are applied in teaching the Arabic language in the fourth year of primary education by analyzing the process of reading activity instructions for this level. For the purpose of answering two important questions: First: What are the principles of social structural theory in education that the curriculum recommends applying? Do these principles exist in the practice of reading activity in the fourth year of primary education?